Leadership and Organizational Challenges, Opportunities, Resilience, and Supports during the COVID-19 Pandemic - Vito, Rosemary; Schmidt Hanbidge, A.; Brunskill, L. (Administration in social work, 2023)
Leaders are coping with multiple challenges during the COVID-19 pandemic and both individual and organizational resilience are critical to successfully manage this turbulent change. This qualitative study employed focus groups and online surveys to explore 25 directors' and managers' experience coping with the pandemic, along with organizational supports and resources, in three mental health/addiction agencies in Canada. Thematic data analysis revealed multiple individual and organizational challenges and opportunities, resilience factors, and supports. These results expand empirical research on resilience factors during turbulent change and are relevant for leaders coping with future crises. Leaders faced multiple individual challenges, including uncertainty, vulnerability, and fear, heavy workloads and difficult decisions, fatigue and stress; these may serve as a caution for future leaders facing unprecedented changes in human services. Organizational challenges included strained internal/external relationships, social isolation, difficulty balancing client/staff safety and service standards; they illustrate the struggle for leaders to balance competing organizational agendas during trying times. Opportunities included risk-taking and adaptability to rapid changes, innovation and creative solutions, internal/external collaboration with partners, leadership development and succession planning for longer-term sustainability. Leaders' individual resilience factors included development of enhanced self-confidence, collaboration, communication and problem-solving skills, compassion and empathy, humility, gratitude, hardiness, perseverance, and patience. Organizational resilience and sustainability can be nurtured through emotional connection and support, organizational culture and teamwork, clear communication, shared decision-making, clear values and mission, and work-home life balance.